2017
DOI: 10.4168/aair.2017.9.2.142
|View full text |Cite
|
Sign up to set email alerts
|

Vγ1+γδT Cells Are Correlated With Increasing Expression of Eosinophil Cationic Protein and Metalloproteinase-7 in Chronic Rhinosinusitis With Nasal Polyps Inducing the Formation of Edema

Abstract: PurposeWe have found that expression of γδT cells is increased in pathological mucosa of chronic rhinosinusitis with nasal polyps (CRSwNP) compared with normal nasal mucosa. This increase is correlated with the infiltration of eosinophils in CRSwNP. Here, we investigated the expression of γδT cells, inflammation and tissue remodeling factors as well as their probable relationships in different types of chronic rhinosinusitis (CRS) in China.MethodsA total of 76 surgical tissue samples that included 43 CRSwNP sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 38 publications
(62 reference statements)
2
16
0
Order By: Relevance
“…Edema formation in NPs has previously been reported to be associated with eosinophil infiltration. 37,38 In this regard our study has shown a positive correlation between edema scores and T H 2-related factors and a negative correlation between edema scores and T H 17-related factors, suggesting that the T H 2 pathway promotes edema formation, whereas the T H 17 pathway inhibits edema formation. Our finding that edema scores in the IL-5 1 IL-17 2 group were greater than those in the IL-5 2 IL-17 1 group further supports this hypothesis.…”
Section: Discussionsupporting
confidence: 51%
“…Edema formation in NPs has previously been reported to be associated with eosinophil infiltration. 37,38 In this regard our study has shown a positive correlation between edema scores and T H 2-related factors and a negative correlation between edema scores and T H 17-related factors, suggesting that the T H 2 pathway promotes edema formation, whereas the T H 17 pathway inhibits edema formation. Our finding that edema scores in the IL-5 1 IL-17 2 group were greater than those in the IL-5 2 IL-17 1 group further supports this hypothesis.…”
Section: Discussionsupporting
confidence: 51%
“…Compared with lower airway inflammation, the functions of γδ T cells in chronic nasal inflammation (eg, chronic rhinosinusitis and AR) are poorly understood. A recent study demonstrated that the messenger RNA (mRNA) levels of γδ T cell Vγ1 genes were upregulated in nasal polyps, which was associated with eosinophilic infiltration and edematous changes . Our previous examination of peripheral blood mononuclear cells revealed a dynamic equilibrium in the number of γδ T cell subfamily members in AR patients before and after allergen‐specific immunotherapy .…”
mentioning
confidence: 96%
“…We speculated that higher expression of MMP-9 could contribute to longer surgery recovery time in patients with CRSwAR. Yang et al [ 40 ] showed that MMP-7 was significantly increased in EOS CRSwNP compared to non-Eos CRSwNP. However, our data showed that MMP-7 expression was higher in CRSsNPwAR group compared to CRSsNPsAR group and no significant difference was observed between CRSwNPsAR group and CRSwNPwAR group.…”
Section: Discussionmentioning
confidence: 99%